A STYLISTICS STUDY OF DISPLACEMENT AND NOSTALGIA IN GULZAR’S MAHAMARI LAGI THI - Jayal, Jyoti; Kumar, Vijay; Vats, Ayush (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The historic reverse migration of Indian migrant labourers, during the first wave of the coronavirus pandemic (COVID-19), revealed the profound socio-economic vulnerabilities faced by this marginalised community. Despite its magnitude, the human suffering associated with this crisis remained largely unheard and underrepresented. Gulzar’s poem Mahamari Lagi Thi emerges as a significant literary response to this unaddressed humanitarian issue, demanding critical attention to the stylistic and thematic strategies through which it articulates migrant anguish. The research aims to examine the literary and stylistic techniques employed in Gulzar’s Mahamari Lagi Thi to foreground the plight, pain, and existential crisis of migrant labourers during the pandemic. It also seeks to explore how themes of nostalgia, displacement, and longing for homeland are used to evoke empathy and social awareness among readers. The paper adopts a literary stylistics approach, integrating textual analysis with concepts drawn from migration and displacement theory. By analysing imagery, symbolism, diction, and narrative voice, the article interprets how Gulzar’s poetic strategies construct meaning and shape readers’ emotional responses. The analysis reveals that Mahamari Lagi Thi effectively blends stylistic devices with socio-cultural realities to create a powerful and realistic narrative of migrant suffering. Gulzar’s use of emotive imagery, understated language, and symbolic references intensifies the sense of loss, nostalgia, and existential uncertainty experienced by migrant labourers. The poem’s interdisciplinary resonance enhances its coherence and deepens its impact on readers. The study concludes that Mahamari Lagi Thi stands as a poignant literary testimony to the migrant crisis during the COVID-19 pandemic. Through its nuanced stylistic construction and thematic depth, the poem not only documents a significant moment in recent Indian history but also functions as a moral and emotional appeal, fostering empathy and social consciousness. In doing so, Gulzar reaffirms the role of literature as a powerful medium for representing silenced voices and collective trauma.